Records of the sultanate of the Sulu Archipelago, Philippines - Sulu Archipelago (Philippines)
Chiefly correspondence of the sultanate of the Sulu Archipelago with colonial officials relating to Spanish and American administration and pacification of the sultanate. Includes photographs.
Collection material in Arabic, with English, Spanish, and Tao Sug.
Formerly cataloged under: Jolo (Philippines). Sultanate correspondence, 1901-1914.
Keywords: Sultanate; Sultans -- Philippines -- Sulu Archipelago; Jolo (Philippines) -- History; Philippines -- History -- 1812-1898.; Philippines -- History -- 1898-1946.; Philippines -- Politics and government; Spain -- Colonies -- Administration; Sulu Archipelago (Philippines) -- History; United States -- Territories and possessions